IMPLEMENTASI EVALUASI PEMBELAJARAN BERBASIS DIGITAL DI SEKOLAH DASAR: STUDI OBSERVASI KUALITATIF PADA SEKOLAH DASAR - Jeise Yufengky; Izzatul Azzahra; Salsabila Arifin; Zafnanda Givani; Ranti Meizatri; Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In elementary education, the quick advancement of information and communication technology has revolutionized how we evaluate learning. Teachers may use digital- based assessments to evaluate pupils more effectively, interactively, and objectively. The goal of this research is to outline how digital-based learning evaluation is implemented in elementary schools, with an emphasis on the kinds of digital media employed, implementation techniques, and difficulties experienced. Through field observations done in six representative elementary schools, including public and private schools in urban and semi-rural environments, this study used a descriptive qualitative methodology. Information was gathered through direct observation, organized teacher interviews, and documentation of online assessment tools. According to the results, digital evaluation media like Google Forms, Wordwall, Quizizz, and instructional videos were frequently utilized for summative and formative assessments. Digital-based evaluation improves student engagement, motivation, and learning efficiency, but there are still issues with infrastructure and digital literacy. Generally speaking, when backed by sufficient resources and teacher proficiency, digital evaluation enhances the overall quality of learning.